Legal Liability of AI-Based Digital Agreements in Indonesian Contract Law - Muhammad Karim Benzema; Diky Dikrurahman (Inovasi Pratama Internasional. Ltd, 2026)
The increasing use of Artificial Intelligence (AI) in digital transactions has transformed the mechanism of contract formation within contemporary commercial activities. AI systems are currently capable of drafting contractual clauses, processing transactional data, and generating automated agreements with minimal human intervention. Such developments raise legal issues concerning contractual validity, legal consent, and the allocation of liability when losses arise from AI-assisted contractual processes. This study examines the construction of legal liability in AI-based digital agreements within the Indonesian legal system. The research employed a normative juridical method using statutory, conceptual, comparative, and analytical approaches. The findings indicate that AI-based digital agreements remain subject to the fundamental principles of Indonesian contract law, particularly the validity requirements stipulated under Article 1320 of the Civil Code, the principle of freedom of contract, and good faith. Indonesian law nevertheless does not recognize Artificial Intelligence as an independent legal subject capable of bearing direct legal responsibility. Liability therefore remains attached to parties exercising control, supervision, operation, or economic benefit from the use of AI systems, including business actors, developers, and electronic system providers. The study further identifies a normative gap within Indonesian positive law concerning AI governance, transparency obligations, and allocation of liability in automated contractual relations. This condition potentially creates legal uncertainty and weakens legal protection for parties involved in AI-assisted transactions. The study offers an integrated liability framework capable of addressing legal uncertainty arising from AI-assisted contractual systems within Indonesian contract law.